(untitled) (International Journal of Management and Sustainability, 2025)
This study aims to identify the primary factors influencing SME participation in CSR practices such as cognition, attitude, and intention utilizing the theory of planned behavior framework. We examine how attitudes toward CSR, subjective norms, and perceived behavioral control (PBC) impact the intention to engage in CSR and the actual implementation of CSR practices. A survey was conducted among manufacturing SMEs in Indonesia. Questionnaires were sent to 360 owners or managers who are key decision-makers for CSR initiatives. The analysis employed Structural Equation Modelling (SEM) to test our hypotheses. The findings indicate that TPB antecedents significantly influence individual intentions to participate in CSR. However, PBC does not directly impact actual CSR engagement. Instead, intention acts as a mediating variable between PBC and actual CSR. Intention does not mediate the relationship between attitudes toward CSR or subjective norms and actual CSR activities. The findings confirm that all three antecedents of the theory of planned behavior significantly influence intention with PBC having the most substantial effect. Practically, the findings can guide stakeholders in overseeing ethical business practices through CSR initiatives. Stakeholders should actively support the intention to implement CSR as this can foster innovation, increase profitability, and create added value for small businesses.